Improving Schoolars’ Listening Skills at SMPN 3 Gunungsari By Using The Song - Suparlan; Fitri Ningsi; Hendra Suryadi (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
The research aims to investigate improvement of the schoolars’ listening skills by using the song, identify the types of songs that are most effective, and examine schoolars’ responses toward song-based listening activities. This reserch used a quantitative descriptive research design and involved 28 of eigth-grade schoolars of SMPN Gunungsari. A questionnaire administered after schoolars participated in listening activities using English songs the data were collected. The questionnaire focused on schoolars’ experiences, preferences, motivation, and perceptions related to listening practice through songs. The collected data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. The results of the research show that the majority of schoolars had positive attitudes toward the use of English songs in listening lessons. Most schoolars agreed that English songs helped them improve their understanding of pronunciation, vocabulary, intonation, and overall listening comprehension. Schoolars also reported higher motivation and enjoyment when learning through songs compared to traditional textbook audio materials. In addition, slow-tempo songs with clear lyrics were found to be the most effective, while fast or unclear songs caused some difficulties for schoolars. In conclusion, English songs are an effective and engaging tool for improving schoolars’ listening skills. To make a more enjoyable and effective learning environment, English teachers are encouraged to integrate suitable English songs into listening activities with appropriate guidance